The blink reflex magnitude is continuously adjusted according to both current and predicted stimulus position with respect to the face. (August 2016) - Wallwork, Sarah B.; Talbot, Kerwin; Camfferman, Danny; Moseley, G.L.; Iannetti, G.D.
Abstract: The magnitude of the hand-blink reflex (HBR), a subcortical defensive reflex elicited by the electrical stimulation of the median nerve, is increased when the stimulated hand is close to the face ('far–near effect'). This enhancement occurs through a cortico-bulbar facilitation of the polysynaptic medullary pathways subserving the reflex. Here, in two experiments, we investigated the temporal characteristics of this facilitation, and its adjustment during voluntary movement of the stimulated hand. Given that individuals navigate in a fast changing environment, one would expect the cortico-bulbar modulation of this response to adjust rapidly, and as a function of the predicted spatial position of external threats. We observed two main results. First, the HBR modulation occurs without a temporal delay between when the hand has reached the stimulation position and when the stimulus happens (Experiments 1 and 2). Second, the voluntary movement of the hand interacts with the 'far–near effect': stimuli delivered when the hand is far from the face elicit an enhanced HBR if the hand is being moved towards the face, whereas stimuli delivered when the hand is near the face elicit an enhanced HBR regardless of the direction of the hand movement (Experiment 2). These results indicate that the top-down modulation of this subcortical defensive reflex occurs continuously, and takes into account both the current and the predicted position of potential threats with respect to the body. The continuous control of the excitability of subcortical reflex circuits ensures appropriate adjustment of defensive responses in a rapidly-changing sensory environment.